A rare case of perineal abscess caused by aerococcus urinae. (2017) - Ha, Lawrence; Niknam, Negin; Mankame, Siddhi; Koshy, Robin
Abstract: Aerococcus urinae, a previously misidentified pathogen, has become increasingly recognized to cause severe and even fatal infections. Aerococcus-related perineal abscess infections have not previously been reported in the literature. Most reported cases of infections caused by Aerococcus are urinary tract infections, bacteremia, and even rare cases of endocarditis. We report an unusual case of a perineal abscess caused by Aerococcus urinae .